Cu (II) tyrosinate complexes containing methyl substituted phenanthrolines: Synthesis, X-ray crystal structures, biomolecular interactions, antioxidant activity, ROS generation and cytotoxicity - Inci, Duygu; Aydin, Rahmiye; Vatan, Ozgur; Huriyet, Huzeyfe; Zorlu, Yunus; Cosut, Bunyemin; Cinkilic, Nilufer (Wiley, 2019)
In this paper, three new copper (II) complexes, [Cu(4-mphen)(tyr)(H2O)]ClO4 (1), [Cu(5-mphen)(tyr)(H2O)]ClO4 center dot 1.5H(2)O (2) and [Cu (tmphen)(tyr)(NO3)]0.5H(2)O (3) (4-mphen: 4-methyl-1,10-phenanthroline, 5-mphen: 5-methyl-1,10-phenanthroline, tmphen: 3,4,7,8-tetramethyl-1,10-phenanthroline and tyr: L-tyrosine), were synthesized and characterized using elemental analyses, FT-IR, ESI-MS, cyclic voltammetry and single-crystal X-ray diffraction. It was found that the complexes adopt a distorted five-coordinate square pyramidal geometry. The interaction of the three complexes with calf thymus DNA was also investigated using UV-visible absorption spectra, ethidium bromide and Hoechst 33258 displacement assay and thermal denaturation. The DNA cleavage activity of the complexes, monitored using gel electrophoresis, showed significant damage of the pUC19 plasmid DNA. Binding activity of bovine serum albumin (BSA) reveals that these complexes can strongly quench the fluorescence of BSA through a static quenching mechanism. The results suggested that interaction of the complexes with DNA occurred through a partial intercalation into the minor grooves of DNA. In addition, interaction of the complexes with bovine serum albumin quenched the fluorescence emission of the tryptophan residues of the protein binding constants and thermodynamic parameters were obtained from the fluorescence quenching experiments at different temperatures. Free radical scavenging activities of the complexes were determined by various in vitro assays such as 1,1-diphenyl-2-picryl-hydrazyl free radicals (DPPH) and H2O2 scavenging methods. In addition, the cytotoxicity of these complexes in vitro on tumor cell lines (Caco-2 and MCF-7) was examined by XTT and showed better antitumor effect on the tested cells. ROS (reactive oxygen species) and comet experiments are consistent with each other and these complexes lead to DNA damage via the production of ROS. The effect of the hydrophobic properties of the synthesized complexes on DNA and BSA binding activities were discussed.
Keywords: Cu (II) complexes; L-tyrosine; methyl substituted phenanthrolines; DNA/BSA interactions; ROS generation and cytotoxicity